'Small but mighty': conditions for prototypicality claims within low-status merger partners - IGorski, I.; Jarosz, S.; Kavanagh, E.; Kersting, A.-M.; Kounov, P.; Velickovic, K.; Rosa, M. (Journal of European Psychology Students, 2015)
Mergers and acquisitions often exhibit asymmetric group structure and dynamics. Minority (low-status) merger partners frequently perceive themselves as less prototypical of the new organisation, potentially hindering corporate development. This research examines three variables – morality, indispensability, and merger patterns, which may influence prototypicality perceptions in minority merger partners. In respective online-based surveys, each of the variables is experimentally manipulated via scenarios and perceptions of relative ingroup prototypicality and indicators of merger support are measured as dependent variables. Ultimately, the aim of the studies is to give an insight into minority perceptions and suggest better practices for human resource management.